Buy Now, Pay Later: Does Paylater Influence Impulsive Buying Among Generation Z? - Ni Made Sukanadi; , Agus Putu Abiyasa (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine the effect of paylater features on impulsive buying behavior among Generation Z. Using an influence analysis method, this study will measure the extent to which paylater affects the impulsive buying behavior of Generation Z in the context of e-commerce. This study adopts a quantitative approach with a survey research design, utilizing an online Google Form. The data analysis technique employed in this study is quantitative analysis, with the analytical tool being the variance-based structural equation model (PLS-SEM). The results of the study indicate that shopping lifestyle, hedonic motivation, and sales promotions have a significant influence on positive emotions and impulsive buying. Additionally, positive emotions were found to act as a mediating variable in the relationship between shopping lifestyle, hedonic motivation, and sales promotions on impulsive buying.